(untitled) (Publicaciones en Ciencias y Tecnología, 2021)
Polyhydroxyalkanoates (PHAs) are biopolymers of bacterial origin that present varieties of applications, given their characteristics of bioabsorbability, hydrophobicity, biocompatibility and biodegradability. Its production and commercialization at present is limited, due to the fact that there are variables in its production process that must be optimized, so that it is an economically attractive process. In this sense, a bibliographic review was carried out based on the consultation of indexed scientific articles, with the purpose of describing the PHAs, exposing the existing classifications, properties, main applications, proposed stages in the manufacturing process and related variables, so that reduce associated manufacturing costs. It was known that the selection of the substrate, in addition to the microorganisms used in microbial synthesis, are one of the most important stages in the biomaterial manufacturing process, since the manufacturing stages and costs associated with the process depend on this.